2021
DOI: 10.1007/s12975-020-00878-x
|View full text |Cite
|
Sign up to set email alerts
|

Reparative System Arising from CCR2(+) Monocyte Conversion Attenuates Neuroinflammation Following Ischemic Stroke

Abstract: Monocytes recruitment from the blood to inflamed tissues following ischemic stroke is an important immune response to wound healing and tissue repair. Mouse monocytes can be endogenously divided into two distinct populations: pro-inflammatory or classical monocytes that express CCR2highCX3CR1low and circulate in blood, and anti-inflammatory or non-classical monocytes that express CCR2lowCX3CR1high and patrol locally. In this study of transgenic mice with functional CX3CR1GFP/+ or CX3CR1GFP/+-CCR2RFP/+, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…We previously established that monocytes infiltrated into the parenchymal tissue of the injured brain, and these cells were converted to M2 phenotype macrophage by cytokine released from microglia, such as IL-4 and IL-13 ( 15 ). Following previous studies, in this study, we investigated the mechanism by which monocyte-derived macrophage infiltrated parenchymal brain tissue during neuroinflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established that monocytes infiltrated into the parenchymal tissue of the injured brain, and these cells were converted to M2 phenotype macrophage by cytokine released from microglia, such as IL-4 and IL-13 ( 15 ). Following previous studies, in this study, we investigated the mechanism by which monocyte-derived macrophage infiltrated parenchymal brain tissue during neuroinflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that pro-inflammatory monocytes migrate shortly after an ischemic stroke and are converted by interleukin (IL)-4 and IL-13 into anti-inflammatory macrophages that attenuate ischemic stroke ( 15 ). However, potential therapeutic targets that regulate the recruitment of monocyte-derived macrophage in neuroinflammation have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…110 Based on the previous monocyte dichotomy, high CCR2 expression may indicate a pro-inflammatory monocyte cluster, potentially playing a negative pro-inflammatory role in the inflammatory cascade response of AIS and exacerbating brain damage. 107 Peripheral immune cells are considered as potential biomarkers of ischemic stroke. 111,112 Among the circulating immune cells, monocytes have been investigated as potential biomarkers.…”
Section: Monoc Y Te Smentioning
confidence: 99%
“…106 In mice, the monocytes can be divided into two distinct populations: pro-inflammatory monocytes expressing CCR2highCX3CR1low, which circulate in the blood, and anti-inflammatory monocytes expressing CCR2lowCX3CR1high, which patrol locally. 107 Park et al found that CCR2highCX3CR1low monocytes recruited to the injured brain undergo cell-dependent conversion to CCR2lowCX3CR1high monocytes, particularly under the influence of IL-13, thereby alleviating neuroinflammation after ischemic stroke. Thus, modulation of monocyte conversion is an important repair strategy for ischemic stroke.…”
Section: Monoc Y Te Smentioning
confidence: 99%
“…[ 14 ] Interleukin (IL), tumor necrosis factor-alpha (TNF-α), and MCP-1 are classic inflammatory factors released by macrophages, which further regulate the release and migration of inflammatory cells, such as neutrophils, natural killer cells, and lymphocytes. [ 15 ] The infiltration of inflammatory cells and cytokines, which were increased in the injured cerebral hemisphere, lead to greater cerebral I/R injury. [ 16 ]…”
Section: The Key Role Of Spleen In Ischemia/reperfusion Injurymentioning
confidence: 99%